Pengaruh Segmentasi Pasar dan Preferensi Konsumen Terhadap Keputusan Pembelian Kue Organik di Bali Buda - Lianita, Ni Ade; Ustriyana, I Nyoman Gede; Anggreni, I Gusti Ayu Agung Lies (Nandur, 2022)
One of the things that need to be considered in doing the marketing of products to be sold is by analyzing market segmentation and understanding the needs and desires of consumers. This is what Bali Buda has done in formulating its marketing strategy in the face of market share competition and sales decline due to the Covid-19 pandemic. The purpose of this study is to analyze the effect of Market Segmentation and consumer preferences on the decision to purchase organic cakes in Bali Buda by using Structural Equating Modeling-Partial Least Square (SEM-PLS). The sample in this study as many as 65 respondents who are consumers of organic cakes that have bought and consumed organic cakes in Bali Buda. The results showed that market segmentation and consumer preferences have a positive and significant effect on purchasing decisions by producing the original sample value of 0.456; 0.417 and p-value of 0.001; 0.002 with a standard error of 5%. This result means that if the market segmentation is properly formed and the preferences of consumers are met, it can affect the high purchasing decisions of organic cake consumers in Bali Buda.